PENERAPAN MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION (AIR) UNTUK MENGATASI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL POKOK BAHASAN RELASI DAN FUNGSI KELAS VIII DI SMP ISLAM AL-MU’IENTAHUN AJARAN 2013/2014 - Asari, Hasim; Setiawan, Toto' Bara; Kristiana, Arika Indah (Department of Mathematics Education , University of Jember, 2016)
Auditory Intellectually Repetition (AIR) was a learning method in which the auditory skill was used. The students had to be able to listen, speak, present, give argument, and give response. Intellectually was that the students had to be able to use their mind set well to find and apply some problem solving related to their difficulties. Repetition was that the students had to do repetition or make an overview of their understanding and knowledge through quiz and final test. This training was aimed to solve the studens' problem in comprehending some questions aftes finished the lesson by using AIR method. This study used two sickles, in which, in every sickle consisted of planning, conducting, observation, and reflection. The method of collecting data was gotten through some attentive activities. These were observation, documdntation, interview, and test. Then, the data was analyzed by using descriptive qualitative an quantitative method. The result of this study shown the students' improvement, namely in the first sickle was 72,50% and the second sicle was 90%. The students' mistake mostly found in taking conckusion. The effective of AIR method in the fist sickle was 32,48% include in effective enough. Whereas in the second sickle, the effective achieved 26,92% include in effective. Thus, AIR learning method was mostly effective to reduce the students' mistake in answering mathematics questions in the lesson of function relation in SMP Islam Al-Mu'ien.